Natureza, resíduos sólidos e educação ambiental: um estudo sobre o município de Francisco Beltrão-PR - Biral, Raquel Biz (2022)
It can be said that the society-nature relationship is determined by the need for material production and according to the level of society development. There is a great difficulty in properly disposing of the waste generated by our society. We question: what is the destination of solid waste from rural areas? What is the influence of Environmental Education in practices of solid waste problems? We reflect on the concept of Nature that underlies social, cultural, economic, and environmental issues. The consolidated concept of nature in Francisco Beltrão is that nature is reduced to a resource for exploitation in the capitalist production process, to meet a demand of consumption. The appropriation of Nature that has been historically consolidated in the city, since its colonization, is the one that mistakenly links rural areas as a synonym of a balanced environment, disregarding that the rural environment has become a great producer and consumer of elements that ultimately generate waste that must be handled with care. We defend the statement that “Between what is said (discourse, laws, decrees) and what is done (practices, actions), there is the imperfect (reality)”. We aim to analyze how Nature is objectified as a resource and how it is consolidated in Solid Waste disposal practices in Francisco Beltrão. The specific objectives are to identify the existence and effectiveness of the collection and proper disposal of rural solid waste; to verify and estimate the amount of waste generated in rural areas, whether domestic or agricultural, and its environmental impact; to verify the participation of public bodies in the implementation and compliance with specific legislation; and to verify how Environmental Education can influence on waste disposal practices as a way of ensuring environmental justice. It is known that the population of rural areas is less dense than the population of intensely urbanized areas, however, it is not null. To fulfill the objectives previously mentioned, the thesis is organized into seven chapters, which are distributed following a historical and dialectical analysis of how the research data is presented. Methodologically, meetings were held with those in charge of the environment secretariat of the city and a questionnaire was created. The public opinion survey was conducted in person, with unidentified participants, according to their presence in the communities visited, and who spontaneously agreed to collaborate. The management of rural solid waste in the city of Francisco Beltrão has sought to consolidate legal initiatives. The attention to workers involved in waste collection is still deficient and requires training and Environmental Education, to be disseminated in society. Environmental justice has as one of its principles and practices to favor the construction of collective subjects and popular organizations, so that they are protagonists in the creation of alternative models of development, whether human, social, environmental, or cultural. Three possibilities of inserting Environmental Education into the management of solid waste in the city are suggested, as a way of stimulating the training of environmental educators.It can be said that the society-nature relationship is determined by the need for material production and according to the level of society development. There is a great difficulty in properly disposing of the waste generated by our society. We question: what is the destination of solid waste from rural areas? What is the influence of Environmental Education in practices of solid waste problems? We reflect on the concept of Nature that underlies social, cultural, economic, and environmental issues. The consolidated concept of nature in Francisco Beltrão is that nature is reduced to a resource for exploitation in the capitalist production process, to meet a demand of consumption. The appropriation of Nature that has been historically consolidated in the city, since its colonization, is the one that mistakenly links rural areas as a synonym of a balanced environment, disregarding that the rural environment has become a great producer and consumer of elements that ultimately generate waste that must be handled with care. We defend the statement that “Between what is said (discourse, laws, decrees) and what is done (practices, actions), there is the imperfect (reality)”. We aim to analyze how Nature is objectified as a resource and how it is consolidated in Solid Waste disposal practices in Francisco Beltrão. The specific objectives are to identify the existence and effectiveness of the collection and proper disposal of rural solid waste; to verify and estimate the amount of waste generated in rural areas, whether domestic or agricultural, and its environmental impact; to verify the participation of public bodies in the implementation and compliance with specific legislation; and to verify how Environmental Education can influence on waste disposal practices as a way of ensuring environmental justice. It is known that the population of rural areas is less dense than the population of intensely urbanized areas, however, it is not null. To fulfill the objectives previously mentioned, the thesis is organized into seven chapters, which are distributed following a historical and dialectical analysis of how the research data is presented. Methodologically, meetings were held with those in charge of the environment secretariat of the city and a questionnaire was created. The public opinion survey was conducted in person, with unidentified participants, according to their presence in the communities visited, and who spontaneously agreed to collaborate. The management of rural solid waste in the city of Francisco Beltrão has sought to consolidate legal initiatives. The attention to workers involved in waste collection is still deficient and requires training and Environmental Education, to be disseminated in society. Environmental justice has as one of its principles and practices to favor the construction of collective subjects and popular organizations, so that they are protagonists in the creation of alternative models of development, whether human, social, environmental, or cultural. Three possibilities of inserting Environmental Education into the management of solid waste in the city are suggested, as a way of stimulating the training of environmental educators.